The use of corn in trimester i pregnant women againts complaints of trimester I pregnant women at Lohia District, Muna Regency, Southeast Sulawesi in 2020 - Hilda Sulistia Alam; Sutrisna Altahirah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: Hemoglobin (Hb) is a protein molecule containing iron from red blood cells and myoglobin in the muscles which functions to carry oxygen from the lungs to all body tissues and brings back carbon dioxide from all body tissues to the lungs to be excreted from the body. Hb level during pregnancy is very important because it affects the condition of the mother and fetus. If the Hb level of pregnant women is low, it can cause anemia. Symptoms of anemia are dizziness, pallor, nausea, vomiting, fatigue, and decreased appetite. One of the foods that are good for pregnant women to consume is corn. It contains vitamins B1, B6, B9, B12, Biotin and pantothenic acid to metabolize carbohydrates, coenzymes, increase endurance, overcome nausea and vomiting, Hb formation and prevent anemia. Objectives  : This study aimed to determine the benefits of corn in trimester I pregnant women against complaints of pregnant women in trimester I. Methods : This research was a quasi-experiment with a pretest-posttest two group design approach in Lohia District, Muna Regency, Southeast Sulawesi in 2020 with simple random sampling and the subjects in this study consisted of 20 in intervention and 20 in controls. The data collection technique was done by using an observation sheet to record the Hb measurement results. The t-test was used as a sample analysis test to determine the benefits of corn. Results : The results showed that in the first trimester of pregnant women, there was a significant increase in Hb levels after being given corn (Zea Mays) with P value = 0.000 <α = 0.05. Conclusion : The benefits of giving corn to trimester I pregnant women against complaints of trimester I pregnant women